EU and USA need broader foundation : the case for a 'transatlantic treaty'. - HELLMAN, Gunther (1994)
Describes NATO as one of the mainstays of European-American relations. Presents three operational alternatives for the future restructuring of relations between the USA and Western Europe, viz.: (1) a bloc formation, (2) a renewed 'transatlantic bargain', or (3) a comprehensive contractual frame.